Do Better Tax Agency Services Improve Taxpayer Compliance? Evidence from Germany - Hechtner, Frank; Blaufus, Kay; Jarzembski, Janine K. (2022)
In many countries, tax agencies are following OECD recommendations and are improving their services to increase voluntary tax compliance. Using a survey of 10,000 individual German taxpayers, we find that better service interaction quality (SIQ) is indeed positively associated with tax compliance. However, there is great heterogeneity in this effect. First, improving SIQ mainly affects the tax compliance of self-preparers who have low tax knowledge and high tax morale, suggesting that tax agency services reduce the unintentional mistakes of these taxpayers. Second, our results show a positive association of SIQ with tax compliance when the perceived coercive power of the tax office is high, suggesting that deterrence and service provision are complementary instruments for increasing tax compliance. Furthermore, an increase in perceived SIQ is associated with a reduction in the probability of appeal. Thus, better services also help to significantly reduce the tax controversy costs for tax administrations and taxpayers